Auto-victimisation et discours politique : émotions, résonance culturelle et mobilisation dans la rhétorique de B. Netanyahou - Eithan Orkibi (Argumentation et Analyse du Discours, 2019)
This article explores the rhetoric of auto-victimization in political discourse. While “victimization” is generally defined as the process by which individuals or group as culturally constructed or socially acknowledged as victim, “auto-victimization” is the discursive practice by which a speaker constructs his or her own image or identity as victim. Drawing on the theoretical framework of the interactionalist approach to victimology in social sciences, the study examines three constitutive dimensions of a political leader, i.e, Benjamins Netanyahu’s rhetoric of auto-victimization in response to corruption charges: emotional mobilization, cultural resonance, and appeal to collective identity. The analysis shows that Netanyahu projects an image of a victim of persecution, while assimilating his personal story to the constitutive narrative of the Israeli right, self-perceived as a historically marginalized and oppressed by the Israeli left. Netanyahu’s auto-victimization thus transforms into a symbolic figure of the Israeli right’s tradition of victimization, and constitutes an emergency call to defend Netanyahu in order to protect the entire political camp. The results of the analysis correspond to the discursive practices observed by cultural victimology, but they also echo some of the rhetorical strategies associated with contemporary populist political discourse.